Nutritional Value of Mulberry (Morus alba) Forage Harvested During Dry and Wet Seasons in Northern Ethiopia - Ebrahim, Assen; Animut, Getachew; Urge, Mengistu; Hailemichael, Aklilu (Indian Journal of Animal Nutrition, 2018)
This study was conducted to evaluate the chemical composition, in vitro dry matter digestibility (IVDMD), in vitro organic matter digestibility (IVOMD) and in sacco DM and nitrogen (N) degradability of leaves and edible branches of mulberry harvested in dry and wet seasons. In sacco DM and N degradability were evaluated using three rumen fistulated crossbred steers (Boran Ã— Friesian). The contents of CP, total ash and NDF contents of mulberry were influenced (P<0.05) by interactions between plant parts (leaves and edible branch) and season. In both the seasons, the CP and ash contents of leaves were higher (P<0.05) than that of the edible branch. For both plant parts, the CP level was higher (P<0.05) in wet season than in dry season. The fibre contents (NDF, ADF, cellulose and ADL) were higher in edible branch than in the leaves and higher (P<0.05) values were recorded for dry season. The mean IVDMD, IVOMD and metabolizable energy values were higher (P<0.05) for leaves (79.2, 74.4% and 11.9 MJ/ kg DM, respectively) than for edible branch (58.2, 55.7% and 9.0 MJ/kg DM, respectively). The corresponding values during wet season were significantly higher(P<0.05) than the values during dry season. Similarly, the mean degradability values of both DM and N were higher (P<0.05) in leaves than in edible branch and these parameters were higher (P<0.05) during wet season.As the nutritive value of mulberry plant was influenced by season, plant parts and their interaction, such factors need to be considered for utilizating mulberry as alternative feed for livestock.